AND ECOLOGICAL FACTORS AND FALLOW PERIOD OF FOREST REHABILITATION AFTER SHIFTING CULTIVATION IN MUONG LAT DISTRICT, THANH HOA PROVINCE - Hong Sinh, Le; Tien Hinh, Vu (Journal of Forestry Science and Technology, 2016)
Determining the relationship between some inventory factors and ecological factors and fallow period of forest rehabilitation after shifting cultivation has very important meaning in proposing effective solutions for reforestation, contributing to the protection of the ecological environment, limiting soil erosion, and soon reached the forest criteria. Results from 95 temporary plots (each plot covering 1000 m2) showed that: number of tree species has a significant and positive relationship with fallow periods, with porosity, soil layer thickness and cover of lianas and shrubs. The density and mean height of trees with total tree height from 2 m have a significant and positive relationship with fallow periods, soil layer thickness and cover of lianas and shrubs. The research results are the basis to determine the time for forests formed and effect measures to forests to restore after shifting cultivation.